Effects of over-expressing the AgGPPS2 gene in Salvia stenophylla (Burch. ex Benth) on terpenoid biosynthesis - Musarurwa, Hannibal Tafadzwa (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.